(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article explores the key contemporary issues of maintaining global peace and security, emphasizing the essential role of international cooperation. It analyzes collective security mechanisms, the contribution of international organizations (UN, OSCE, SCO, NATO), and the impact of transnational threats such as terrorism, cyber risks, nuclear proliferation, migration and ecological crises. The study highlights how diplomacy, confidence-building measures and multilateral dialogue shape sustainable peace.